Diketopyrrolopyrrole pigment core@multi-layer SiO2 shell with improved photochemical stability. (September 2018) - Fabjan, Erika Švara; Saghi, Zineb; Midgley, Paul A.; Otoničar, Mojca; Dražić, Goran; Gaberšček, Miran; Škapin, Andrijana Sever
Abstract: A model organic pigment (diketopyrrolopyrrole) is encapsulated by a silica coating in order to improve its photochemical stability. Unlike in previous works where single-layer silica coatings were used for similar purposes, we here propose creation of a multi-layer silica shell synthesized via in-situ sol-gel method, which should significantly improve the homogeneity and thus the protection ability of the coating. This is done by repeating the basic two-step process (pigment surface modification and silica encapsulation) several times, creating the final protective shell in a layer-by-layer fashion. The compositional and structural properties of the prepared coatings is studied using Fourier-transform infrared spectroscopy, differential thermal and thermogravimetric analysis, nitrogen adsorption measurements and transmission electron microscopy. Photochemical stability of non-encapsulated and encapsulated pigment particles is evaluated via the so-called fast-irradiation method. Various correlations between the essential coating properties, such as thickness, porosity, SiO2 content, and the corresponding photochemical stability of the samples are established and discussed in detail. As a whole, our results confirm the basic hypothesis, that multiple-layered silica shells show improved pigment protection ability in comparison to the single-layer coatings. Graphical abstract: Highlights: Multi-layer SiO2 encapsulation was performed via in-situ sol-gel synthesis. The surface of the pigment particles was successfully covered by silica shells. The photochemical stability of the pigment was significantly improved. Protection is more affected by number of layers rather than by SiO2 concentration. Higher silica precursor concentrations lead to considerable porosity of shells.